Cobwebs, Rational Expectations and Futures Markets - Stein, Jerome L. (The Review of Economics and Statistics, 1992)
In the absence of futures markets, cobweb cycles and other behavior inconsistent with Muth rational expectations persist for long periods of time. When futures markets are introduced in commodities, these markets behave in a manner much more consistent with Muth rational expectations. By contrast, despite the existence of active forward and futures markets, the Muth rational expectations hypothesis is rejected in the financial and foreign exchange markets. The aim of this paper is to suggest an explanation of how futures markets change the structure of the supply response. Copyright 1992 by MIT Press.